New data, new approaches and new evidence: A policy synthesis - Arndt, Channing (Wiley, 2018)
The Republic of South Africa faces the imperative of escaping economic stagnation. This article seeks to synthesise results from a series of research efforts, including but not limited to the articles presented in this special issue, and consider policy options for escaping economic stagnation. The focus is on South Africa and South African policies yielding relatively quick dividends in terms of growth and taking the rest of the world as given. Four broad implications are presented. These could form part of a concerted effort to escape from South Africa's long running economic malaise.